Expression of Thrombospondin 1 on the Surface of Activated Platelets Mediates their Interaction with the Heavy Chains of Human Kininogens through Lys 244-Pro 254 - DeLa Cadena, Raul A.; Kunapuli, Satya P.; Walz, Daniel A.; Colman, Robert W. (Thrombosis and Haemostasis, 1998)
Platelet thrombospondin (TSP1) forms a complex with high (HK) and low (LK) molecular weight kininogens. We isolated a proteolytic fragment from HK and LK heavy chains (12 kDa) recognized by TSP1 with a N-terminal sequence, K244ICVGCPRDIP254. Lys244-Pro254 oxidized to cyclic form prevented binding of 125I-LK to TSP1. This effect was abolished by reduction and alkylation. Oxidized peptide KICVGCPRDIP (100 μM) reversed the known inhibitory effects of LK or HK (1 μM), on thrombin-induced platelet activation, suggesting this peptide forms part of the cell binding site on HK and LK for activated platelets. KICVGCPRDIP completely inhibited the binding of 125I-LK to activated platelets. However, the peptide only partially inhibited binding of 125I-HK to platelets, suggesting an additional binding site on the HK light chain. Fluorescein-labeled KICVGCPRDIP bound directly and specifically to activated platelets. A monoclonal antibody directed to TSP1 partially inhibited the binding of 125I-HK to activated but not inactivated platelets. We conclude residues Lys244-Pro254 on kininogen heavy chain is responsible for binding to thrombospondin on the surface of activated platelets.